REPRESENTASI SIKAP TOLERANSI BERAGAMA SISWA (STUDI KASUS KELAS VII SMPN 1 KARAWANG BARAT) - Robiah Umi Hakim; Achmad Junaedi Sitika; Nurhasan Nurhasan (Tasyri’: Jurnal Tarbiyah – Syari’ah Islamiyah, 2025)
The results of this study indicate that students' understanding and attitude of religious tolerance at SMPN 1 West Karawang is quite good and Islamic education learning at SMPN 1 Karawang Barat is sufficient to provide understanding and tolerance for students. Understanding and attitude of religious tolerance among students include: (a). Tolerance attitude, (b). Recognition of differences between people, as well as with other religions, (c). Difference as a gift from Allah SWT, (d). Always respect the adherents of other religions to build a peaceful world. Conditions of tolerance between students and students, students and teachers, teachers and teachers, are harmonious. This study aims to provide an overview of how the understanding and attitude of religious tolerance of students at SMPN 1 West Karawang.